2008
DOI: 10.1097/gim.0b013e31815f6eac
|View full text |Cite
|
Sign up to set email alerts
|

Technical standards and guidelines for reproductive screening in the Ashkenazi Jewish population

Abstract: These Technical Standards and Guidelines were developed primarily as an educational resource for clinical laboratory geneticists to help them provide quality clinical laboratory genetic services. Adherence to these standards and guidelines is voluntary and does not necessarily assure a successful medical outcome. These Standards and Guidelines should not be considered inclusive of all proper procedures and tests or exclusive of other procedures and tests that are reasonably directed to obtaining the same resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Targeted DNA analysis for the seven mutations on all 4,325 samples showed that there were 188 carriers, with mutation distribution frequencies similar to published results (Monaghan et al 2008;Scott et al 2010) (Table 1). Of the 175 carriers of disease-causing mutations, 172 were platelet carriers, while three were platelet inconclusive.…”
Section: Resultssupporting
confidence: 84%
“…Targeted DNA analysis for the seven mutations on all 4,325 samples showed that there were 188 carriers, with mutation distribution frequencies similar to published results (Monaghan et al 2008;Scott et al 2010) (Table 1). Of the 175 carriers of disease-causing mutations, 172 were platelet carriers, while three were platelet inconclusive.…”
Section: Resultssupporting
confidence: 84%
“…These rates are generally accepted for the majority of diseases [DeMarchi et al, 1996; Eng and Desnick, 2001; Eng et al, 1997; Gross et al, 2008; Monaghan et al, 2008], and the detectabilities of the five disorders recently included in the panel were based on previous reports of affected AJ families [Anderson et al, 2004; Ben-Yosef et al, 2003; Brownstein et al, 2004; Hong et al, 2003; Ness et al, 2003; Nestorowicz et al, 1996; Shaag et al, 1999]. Their respective detectability rates were used to determine the residual risk for each disease among the 100% AJ screenees, which are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The success of this prevention strategy in the AJ community has been remarkable. Today, the birth of affected children with these diseases is rare [Lerner, 2009] as the screening programs have essentially become ‘standard of care’ by guidelines and recommendations of the ACOG [ACOG, 2004; 2009] and ACMG [Gross et al, 2008; Monaghan et al, 2008]. …”
Section: Discussionmentioning
confidence: 99%
“…In the few instances where the carrier frequency was lower than expected ( Table 1), it was still more than the 1% frequency recommended for screening by the American College of Medical Genetics and Genomics. 15 A different situation was observed for the non-Jewish subgroups because there were no previous data on carrier frequency based on relatively large numbers of screened individuals. The first-year results of the expanded program indicate that the carrier rates of SMA were high in the three non-Jewish subgroups.…”
Section: Discussionmentioning
confidence: 98%